PENGARUH TARI PETANG MEGANG TERHADAP MOTORIK KASAR ANAK USIA 5-6 TAHUN DI TK KEMALA BYANGKARI 2 BRIMOB KELOMPOK B PEKANBARU - Syaroh Azahro; Ria Novianti; Hukmi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Based on the results field observation of gross motoric of students have not developed optimally, so it is necessary to apply the petang megang dance application. This study aims to determine the effect of petang megang dance on rough motoric aged 5-6 years old in Kemala 2 Brimob kindergarten Pekanbaru. The sample in this study was 20 students. The data collection technique in this study is observation. Technique of data analysis using t-test by using program of SPSS 20. The research hypothesis is petang megang dance activity have influence to gross motoric of child aged 5-6 years old in Kemala 2 Brimob kindergarten Pekanbaru. This can be known from the analysis of data obtained t count = 21,904 and Sig. (2-tailed) = 0.000. Because Sig. (2-tailed) = 0.000 <0,05 it can be concluded that there is a significant rough motoric significantly after the application of petang megang dance in the learning process. So it means Ho is rejected and Ha accepted which means there is a very significant difference between before and after doing experiments by applying the petang megang dance. The influence of petang megang dance on gross motoric ability age 5-6 years old in Kemala 2 Brimob Kindergarten Pekanbaru by 55,84%.Keywords: Petang Megang Dance, Gross Motor Ability.